Low rate of infectious mortality omitting fluoroquinolone prophylaxis in high-risk hematological patients, a single centre experience - Santoni, Adele; Malchiodi, Margherita; Zappone, Elisabetta; Cartocci, Alessandra; Sicuranza, Anna; Pacelli, Paola; Zuanelli Brambilla, Corrado; Defina, Marzia; Tumbarello, Mario; Bocchia, Monica (Frontiers in Microbiology, 2025)
IntroductionIn hematological patients treated with intensive chemotherapy (CHT), febrile neutropenia (FN) is the primary cause of non-relapse mortality (NRM) due to infections that occur during prolonged neutropenia. Fluoroquinolone (FQ) prophylaxis is still recommended by several guidelines for neutropenic patients because it helps reduce bacterial infection rates and fever episodes, although it does not affect infection-related mortality (IRM). However, in the era of multi-drug resistance (MDR), the use of FQs should be evaluated carefully.MethodsWe present a retrospective, single-center study based on real-life data that includes 512 intensive chemotherapy treatments and the occurrence of prolonged neutropenia in 236 high-risk (HR) hematological patients treated without FQ prophylaxis.ResultsIn the entire cohort, we recorded FN in 80.5% of the cases. Among these, 33.7% were attributed to fevers of unknown origin, 45.4% were associated with bloodstream infections (BSIs), 9.0% involved bacterial organ infections, 13.6% were due to fungal infections, and 3.4% were linked to viral infections. Septic shock was observed in 7.6% of the patients. Although we documented a high infection rate, the IRM and overall mortality rates were 3.0% (7/236) and 9.3% (22/236), respectively. These rates are comparable to those found in settings where FQ prophylaxis is used.ConclusionAlthough our cohort was small, our results advocate for the exclusion of FQ prophylaxis in HR hematological patients, without increasing the IRM rate and addressing the risk of life-threatening MDR infections. While we believe it is mandatory to have an efficient protocol for the prompt treatment of FN, our data should encourage hematologists to limit the use of FQ prophylaxis.